Multi-factor analysis of failure of renal replacement therapy in acute renal failure developed after cardiac surgery - Nawrocki, Pawel; Szwedo, Ireneusz; Tyc, Joanna; Hawrysz, Anna; Janiak, Kamila; Cichoń, Romuald (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction: Acute renal failure (ARF) is a rare (2-15%), but severe complication of cardiac surgery with overall mortality reaching 40-80%. In order to save patients’ lives they are treated with renal replacement therapy (RRT). The aim of our study was to assess the impact of different perioperative factors on mortality among patients treated with RRT because of acute renal failure, which occurred as a complication of a heart surgery. Material and methods: Retrospective analysis included 45 patients, operated in the years 2009-2013, who underwent renal replacement therapy in order to treat postoperative ARF. The perioperative factors were analysed in two groups: group 1 – patients who died before discharge; and group 2 – those who survived until hospital discharge. Results: Forty-five of 3509 cardiac surgical patients (1.25%) required RRT after the surgery. A total of 23 (51.11%) died before discharge (group 1). Patients in group 1 were characterised by older age (70.21 vs. 67 years), higher mean EuroSCORE value (9.28 vs. 7.15) (p < 0.05), higher percentage of concomitant surgery (63.63% vs. 28.57%) (p < 0.05) and of admission of catecholamines in the postoperative period (100% vs. 68.42%) (p < 0.005), and higher mean urea blood level prior to RRT initiation (156.65 vs. 102.54 mg/dl) (p < 0.05). Conclusions: The statistically relevant death predictors proved to be: high EuroSCORE, concomitant surgery, and high urea level at RRT initiation and admission of catecholamines in the postoperative period. After conformation in further studies, those factors may prove useful in stratification of death risk among surgical patients requiring RRT.